Respuesta :

The value of [tex]a[b(x)][/tex] is [tex]3x-39[/tex]

Explanation:

Given that the functions [tex]a(x)=3x-12[/tex] and [tex]b(x)=x-9[/tex]

We need to determine the value of [tex]a[b(x)][/tex]

The value of [tex]a[b(x)][/tex] can be determined by substituting [tex]x=x-9[/tex] in the function  [tex]a(x)=3x-12[/tex]

Thus, we have,

[tex]a[b(x)]=a(x-9)[/tex]

Let us substitute the value [tex]x=x-9[/tex] in the function [tex]a(x)=3x-12[/tex]

Substituting [tex]x=x-9[/tex] in the function [tex]a(x)=3x-12[/tex] , we get,

[tex]a[b(x)]=3(x-9)-12[/tex]

Multiplying the terms, we get,

[tex]a[b(x)]=3x-27-12[/tex]

Adding the like terms, we have,

[tex]a[b(x)]=3x-39[/tex]

Thus, the value of [tex]a[b(x)][/tex] is [tex]3x-39[/tex]

Answer:

3x - 39

Step-by-step explanation:

a(b(x)) = 3b(x) - 12

= 3(x - 9) - 12

= 3x - 27 - 12

= 3x - 39